Nazewnicze przejawy "nowej" tożsamości. O roli onimów w oswajaniu przestrzeni miejskiej w powojennej Zielonej Górze i okolicy = Onomastic symptoms of new identity - Żuraszek-Ryś, Iwona (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The basic purpose of this article is the analysis of the methods of polonisation of various onims as expressions of overcoming the surrounding strangeness and creation of new identity of the settlers who came to Zielona Gora and its vicinity.
Keywords: tożsamość; tożsamość aktywna; tożsamość pasywna; tożsamość deliberatywna; memetyka; identyfikacja; samoidentyfikacja; język; językoznawstwo; językoznawstwo polskie